2010
DOI: 10.1007/s11999-009-1187-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Adverse Reaction Associated with Low-carbide Metal-on-metal Bearings in Total Hip Arthroplasty

Abstract: The conventional histologic and immunohistochemical findings in tissues retrieved from failed THAs with low-carbide metal-on-metal bearings are consistent with a link between hypersensitivity and osteolysis with low-carbide bearing couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…Extensive soft tissue damage is more commonly encountered in MoM hips revised for aseptic loosening than hips with other bearing surfaces with severe bone loss reported as well [1,8]. The extent of adverse local tissue response confronted at the time of revision poses genuine concern for outcome as it pertains to fixation, stability, and, potentially, infection [7,10,13,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive soft tissue damage is more commonly encountered in MoM hips revised for aseptic loosening than hips with other bearing surfaces with severe bone loss reported as well [1,8]. The extent of adverse local tissue response confronted at the time of revision poses genuine concern for outcome as it pertains to fixation, stability, and, potentially, infection [7,10,13,39].…”
Section: Resultsmentioning
confidence: 99%
“…Although initial reports were satisfactory [5,14,22,28,29], subsequent research demonstrated unacceptable early failure rates of monoblock MoM THAs, resulting in a substantial revision burden [2-4, 6, 7, 10, 12, 13, 15, 18, 19, 21, 24, 25, 27, 30, 32, 33, 36]. These revisions can be complicated by extensive soft tissue and bony defects, persistence of adverse local tissue reaction as well as problems associated with the general need to reduce the head size at the time of revision, perhaps increasing the likelihood of dislocation [1,3,7,10,13,18,19,23,25,31,33]. Previous studies reporting on the early complications after these revisions are limited and generally of small number [3,10,31,35].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of inflammation was assessed qualitatively by a board-certified pathologist familiar with revision total joint arthroplasty. The diagnosis of ALVAL was made when an inflammatory infiltrate of lymphocytes and macrophages was seen in a perivascular distribution [2,13,15]. Areas of necrosis were also noted if present.…”
Section: Methodsmentioning
confidence: 99%
“…The diffusely distributed chronic inflammation is often composed mainly of T-lymphocytes, whereas lymphoid aggregates are commonly combinations of B-and T-cells with occasional plasma cells [25,29,33]. These findings appear to be more common in either failed metal-on-metal hips [2,10,43] or in cases of failed nonmetal-on-metal hips in which metal particles can be identified [17]. Histologic features suggestive of an immune reaction appear to be very uncommon in cases of failed ceramic-on-ceramic implants unless there is coexisting evidence of wear and/or corrosion at a modular interface.…”
Section: Are the Patterns Of Inflammationmentioning
confidence: 90%